Lokajībane Bāṃlāra laukika dharmasaṅgīta o dharmīẏa melā - Brhma, Trpti (Trpti Brahma ; Prāptisthāna Tārakeśvara Buka Shṭala, 1983)
On the folk deities, festivals, and songs of various religious cults and sects in West Bengal.